Mobility outcomes and associated factors of acute geriatric care in hospitalized older patients: results from the PAGER study - Werner, Christian; Bauknecht, Laura; Heldmann, Patrick; Hummel, Saskia; Günther-Lange, Michaela; Bauer, Jürgen M.; Hauer, Klaus (European geriatric medicine, 2023)
Purpose: To examine distinct mobility outcomes (locomotor capacity, physical activity, life-space mobility) of acute geriatric care (AGC) in acutely hospitalized older adults and identify predictors associated with these outcomes. Methods: The PAGER study was designed as a prospective observational study. Mobility outcomes of 107 hospitalized older patients (age = 83.2 ± 6.4 years, female: n = 68, 63.6%) receiving AGC were measured at hospital admission and discharge. Locomotor capacity was assessed with the Short Physical Performance Battery (SPPB), 24-h physical activity (step count) with an activity monitor, and life-space mobility with the Life-Space Assessment in Institutionalized Settings (LSA-IS). Baseline demographical, clinical, physical, cognitive, and psychological characteristics were analyzed as candidate predictors of mobility outcomes. Results: SPPB (median [interquartile range] 4.0 [2.8–5.0] pt. vs. 5.0 [3.0–6.3] pt.), step count (516 [89–1806] steps vs. 1111 [228–3291] steps), and LSA-IS total score (10.5 [6.0–15.0] pt. vs. 16.3 [12.0–24.1] pt.) significantly improved during AGC (all p < 0.001). Adjusting for baseline status, frailty was identified as an independent negative predictor of SPPB, step count, and LSA-IS at discharge (p = 0.003–0.005). Barthel Index was also independently positively associated with step count (p = 0.017) at discharge, as was the mean daily PA level with SPPB (p = 0.027) at discharge, both independent of baseline status. Conclusion: AGC improves distinct mobility outcomes in hospitalized older patients. Frailty was consistently found to be an independent negative predictor of all mobility outcomes. Frailty assessment in AGC may be important to identify patients at risk for decreased treatment gains in mobility. Early PA promotion in AGC seems to be beneficial in improving patients’ locomotor capacity.